Thermochemical upgrading of Refuse Derived Fuel - Nobre, Catarina Pereira (2019)
The main objective of this thesis was to study Refuse Derived Fuel (RDF) upgrading by torrefaction and carbonization and to evaluate composition, fuel properties and adsorbent properties of the produced RDF chars RDF is a solid fuel produced from non-hazardous wastes, such as municipal solid wastes, construc-tion and demolition wastes or regular industrial wastes, and it is destined for energy production through incineration or co-incineration. Despite the processing, RDF still exhibits unattractive fuel properties, namely high heterogeneity, high moisture and ash contents and low grindability. In a first approach, torrefaction (200-300 ºC) and carbonization (350 and 400 ºC) were applied to an industrial RDF sample, at a laboratory scale, using residence times between 15 and 60 minutes. The produced chars were characterized for their proximate, elemental and mineral compositions, heating value and leaching behavior. The increase in temperature and residence time showed a positive effect on the decrease in volatile matter and increase in fixed carbon content, as well as carbon content and high heating value (HHV). Leaching tests of the produced chars showed that heavy metals are better retained by the char matrix than within the raw RDF. For temperatures in the torrefaction range, process energy yields were higher than 96.3 % and process energy efficiencies were higher than 85 %. Never-theless, the HHV of these RDF chars were lower than 19.4 MJ.kg-1. In the carbonization range, RDF chars presented HHV in the range of 20.1 to 26.2 MJ.kg-1, with energy yields from 84.5 to 91.7 % and process energy efficiencies from 70.8 to 79.2 %. Torrefaction and carbonization tests were also carried out on a pre-pilot scale at 300 and 400 °C, and all products, namely char, condensates and permanent gases were collected and characterized. Chars showed high carbon contents (61.6 % and 80.2 %, 300 ° C and 400 ° C, respectively) and high calorific values (19.9 MJ.kg-1 and 23.5 MJ.kg-1, at 300 °C and 400 °C, respectively). Nevertheless, the ash content of the produced chars increased when compared to the raw RDF, reaching a maximum value of 28.8 wt.%. The thermal treatment caused the organic chlorine present in the RDF to be converted into inor-ganic species which could be removed by washing with water at room temperature. Gaseous emissions were mostly composed of carbon dioxide and carbon monoxide, with lower amounts of methane and hydrogen. The process condensates showed very high COD values and consisted mainly of oxygenated organic compounds, such as acids, furans and phenols. Although the chars produced by torrefaction and carbonization have presented improved fuel prop-erties, hydrothermal carbonization was also tested in order to validate its potential in the production of hydrochars with reduced ash and chlorine contents. The effects of process temperature (250-300 °C), residence time (30 min and 120 min) and solid-to-water ratio (1:15 and 1:5) on the main characteristics of the hydrochars and process waters were evaluated. The hydrochars had a low ash content (3.3 % at 300 °C and 120 min) and good heating values (28.1 MJ.kg-1 at 275 °C and 120 min). The HTC process also revealed a maximum dechlorination efficiency of 55 % at 300 °C for 120 min. The energy efficiency calculations showed that the conditions of 275 °C, 30 minutes with a solid-to-water ratio of 1:5 had lower energy requirements (5.6 MJ), presenting a positive net energy (8.5 MJ) and a higher process efficiency (52.6 %). The process waters presented acid pH, high COD (maximum 27.2 gO2.L-1) and significant concentrations of total phenolic compounds and total reducing sugars. Several organic com-pounds have been identified in process waters, mainly organic acids, alcohols, furan derivatives, phe-nolic compounds and aromatic hydrocarbons. Remediation of the HTC process water was attempted through chemical precipitation and adsorption using activated carbon and RDF derived char. Although removal efficiencies for COD and phenolic compounds were higher for activated carbon, RDF char may be a more sustainable adsorbent to be used in the treatment of these liquid effluents, due to its availability and low cost when compared to activated carbon. The evaluation of the energetic valorization of RDF char by gasification was carried out at a pre-pilot scale using pellets of pine waste fortified with 5 % and 10 % of RDF char. The gasification tests were carried out at the temperatures of 800 and 850 °C and equivalence ratios of 0.25 and 0.30. The product gas yield ranged from 1.5 to 2.5 m3.kg-1 and was higher for an equivalence ratio of 0.25. The carbon conversion efficiency and the cold gas efficiency ranged from 60.4 to 96.1 % and 42.2 to 73.5 %, respectively. The pellets with RDF char had a better gasification performance at 850 ºC and ER 0.25. The incorporation of RDF char increased the concentrations of heavy PAHs in the gasification tars. Finally, the material valorization of the RDF char was tested through its use as a low-cost adsorbent for the removal of the dye methylene blue or the heavy metal chromium (VI) from aqueous effluents. The experiments were carried out in batch and column modes and process parameters were varied, namely, contact time, solution pH, adsorbent mass, contaminant concentration, test temperature or col-umn height. RDF char showed potential to remediate methylene blue, and it has been found that the adsorption may follow a chemical adsorption mechanism. Activation of the RDF char by extraction with aqueous KOH improved its removal efficiency towards both analytes.